ASSESSING NEWLY GRADUATED ACCOUNTING STUDENTS’ PROFICIENCY ON THE USE OF ACCOUNTING SOFTWARE IN SELECTED UNIVERSITIES IN NIGERIA: A FOCUS ON 2019/2020 GRADUATES (Journal of Contemporary Issues in Accounting, 2023)
This study assessed the level of understanding of Accounting Graduates on the use of accounting software in selected Universities in Nigeria. The specific objectives include to: examine the degree of incorporation of accounting software in Education curriculum of selected Universities in Nigeria, ascertain the extent of proficiency in the use of accounting software by graduating students in accounting of selected Universities in Nigeria and to determine the extent to which graduating students in accounting of selected universities in Nigeria, understand the relevance of accounting software in today’s organizational management. The population of the study covered graduating students in accounting department of six federal Universities in Nigeria. Descriptive research design was used and simple random sampling technique was adopted in this study for selection of the sample size. Data was collected using structured questionnaire administered to a sample of 290 respondents. The study concludes that there is a low degree of incorporation of accounting software into Accounting Education Curriculum of selected Universities in Nigeria. Furthermore, the study concludes that graduating students of accounting of selected Universities in Nigeria do not have proficiency in the use of accounting software. Also that graduating students of accounting have a very strong understanding of the relevance of accounting software in today’s organizational management. Based on the findings from this research study, the under listed were recommended: The National Universities Commission (NUC) and relevant educational bodies should integrate (in all higher institution) in accounting curriculum at all level, a practical course on accounting packages and IT knowledge and skills. Furthermore, they should put in place a practical examination on the use of accounting software for accounting degree exams. This would improve the practical experience of young graduates and make them more employable in the 21st century business environment. NUC should ensure strict adherence to the ICT integrated accounting curriculum by the higher institutions both public and private. This can be enforced by denying accreditation to non-compliant institutions.
Keywords: Accounting education; Curriculum; Accounting software; Graduates